2017
DOI: 10.1038/s41598-017-00276-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity interval training and moderate-intensity continuous training on glycaemic control and skeletal muscle mitochondrial function in db/db mice

Abstract: Physical activity is known as an effective strategy for prevention and treatment of Type 2 Diabetes. The aim of this work was to compare the effects of a traditional Moderate Intensity Continuous Training (MICT) with a High Intensity Interval Training (HIIT) on glucose metabolism and mitochondrial function in diabetic mice. Diabetic db/db male mice (N = 25) aged 6 weeks were subdivided into MICT, HIIT or control (CON) group. Animals in the training groups ran on a treadmill 5 days/week during 10 weeks. MICT gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
2
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 67 publications
7
45
2
6
Order By: Relevance
“…High exercise intensity significantly increases cardiac and skeletal muscle mass. In this study, the intensity and length of our exercise likely was a moderate-high-intensity continuous training regimen compared with the exercise training protocol used by Chavanelle et al [25]. Moreover, daily and sustainable physical activity is feasible and effective for preventing excessive weight gain [12].…”
Section: Discussionmentioning
confidence: 98%
“…High exercise intensity significantly increases cardiac and skeletal muscle mass. In this study, the intensity and length of our exercise likely was a moderate-high-intensity continuous training regimen compared with the exercise training protocol used by Chavanelle et al [25]. Moreover, daily and sustainable physical activity is feasible and effective for preventing excessive weight gain [12].…”
Section: Discussionmentioning
confidence: 98%
“…animal is placed onto a treadmill for a specific period). Many exercise training studies have been employed using a variety of animal models of diseases that include HF, 164,173,174 diabetes 175,176 and neurodegenerative diseases. 177 Beside the classical animal models (mouse and rat) used to analyse the effect of exercise training on molecular and physiological parameters, other species have been used more recently such as drosophila and zebrafish.…”
Section: Sense and Nonsense Of Animal Modelsmentioning
confidence: 99%
“…Researchers have shown that exercise increases PGC-1α levels in skeletal muscle and increases the muscle-bearing FNDC5 membrane protein that results in the production of irisin (Schnyder and Handschin, 2015). AMPK activation during exercise is one of the factors involved in increasing PGC-1α and irisin levels (Chavanelle et al, 2017). AMPK activation leads to the phosphorylation of PGC-1α as a modifier of FNDC5 and irisin secretion (Dinas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The eccentric resistance training is likely to activate the PGC-1α activating signals, which may trigger a signal cascade to change the phenotype of the adipose tissue. Eccentric resistance training leads to energy consumption and heat production by increasing muscular tissue to fat tissue ratio and increasing UCP1 (Chavanelle et al, 2017), thus increasing PGC-1α, FNDC5 and irisin (Dinas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%